Entomofauna associated with cowpea Vigna unguiculata (L.) Walp., assessment damages caused by insect pests and predators of Ootheca mutabilis Sahlberg (Coleoptera : Chrysomelidae) in south of Côte d’Ivoire - Landry, Ossey Christian; Nondenot, Aboua Louis Roi; Adagba, Obodji; Christian, Tano Djè Kevin (IJRDO-Journal of Applied Science, 2017)
The necessity to control the insect pests of cowpea (Vigna unguiculata) crops has led to aninventory of insects and assessment of damage caused by pests of this plant. This study wasconducted in Adzopé situated in south of Côte d'Ivoire from march to may 2014. Catcheswere made twice per a week, manually with pliers applying technique of mowing with sweepnet and the plants have been inspected to identify damage caused by pests. In total, 44 specieshave been identified, distributed in 29 families and 9 orders. During the sampling period,2316 insects were collected. The highest number (927 insects) was recorded at fruiting stagerepresenting 40.03 % of the total catch. Ootheca mutabilis was the most abundant species atthe stage before flowering and flowering stage with respectively relative abundances of 39.54and 30.25 %. Megalurothrips sjostedti was majority at the fruiting stage with a relativeabundance of 29.99 %. The analysis of the frequency of occurrence revealed that O. mutabiliswas ubiquist species (frequency of occurrence = 100 %) on the crop. Defoliator insects causedthe most serious damage at the before flowering stage and flowering stage with respectivelyattack rates of 78.65 and 96.35 %. At fruiting stage, the highest attack rate (45.83 %) wasinduced by sucking insects. Among the insects inventoried, three species (Rhinocorisalbopilosus, R. rapax and R. bicolor. (Heteroptera : Reduviidae) have been identified aspredators of O. mutabilis adults.